If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -6 + -5b + -5 = 0 Reorder the terms: -6 + -5 + 2b + -5b = 0 Combine like terms: -6 + -5 = -11 -11 + 2b + -5b = 0 Combine like terms: 2b + -5b = -3b -11 + -3b = 0 Solving -11 + -3b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -3b = 0 + 11 Combine like terms: -11 + 11 = 0 0 + -3b = 0 + 11 -3b = 0 + 11 Combine like terms: 0 + 11 = 11 -3b = 11 Divide each side by '-3'. b = -3.666666667 Simplifying b = -3.666666667
| -6x-36=-2(-3+6x) | | 48r^5b^8+18r^4=0 | | 180=(2x^2-2)x | | 112x^4-280x^3+175x^2=0 | | -6x-18=-108 | | 180=2x^2-2x | | ln(x)-x=35 | | 5x^2=3x^2+50 | | 2x-25=12x+60 | | 1/4M8 | | 8(7a+2)-6a=-2a-36 | | 2=(4y+1) | | 4/5x=6/5 | | g=4t+6 | | 4=16+6x | | 0=80x^3-45x | | 92/100 | | 9q^2-64=0 | | g(x)=80x^3-45x | | 4y+14=6y-2 | | 3x+x^3=108 | | 24a^3-168a^2+294a=0 | | 2cos^2x-9cosx=5 | | 14+2x=56 | | 10x=9x+4 | | 0=-16t^2+20t+0.5 | | 4(4x+19)-3x=0 | | 3x^2-144x+35=0 | | (H^4)= | | x^4-8x^3-16x^2+16x-16=0 | | -16x+72-3x=0 | | 90+(5x-2)=180 |